Aminoglycoside-Induced Cochleotoxicity: A Review - Jiang, Meiyan; Karasawa, Takatoshi; Steyger, Peter S. (Frontiers in Cellular Neuroscience, 2017)
Aminoglycoside antibiotics are used as prophylaxis, or urgent treatment, for many life-threatening bacterial infections, including tuberculosis, sepsis, respiratory infections in cystic fibrosis, complex urinary tract infections and endocarditis. Although aminoglycosides are clinically-essential antibiotics, the mechanisms underlying their selective toxicity to the kidney and inner ear continue to be unraveled despite more than 70 years of investigation. The following mechanisms each contribute to aminoglycoside-induced toxicity after systemic administration: (1) drug trafficking across endothelial and epithelial barrier layers; (2) sensory cell uptake of these drugs; and (3) disruption of intracellular physiological pathways. Specific factors can increase the risk of drug-induced toxicity, including sustained exposure to higher levels of ambient sound, and selected therapeutic agents such as loop diuretics and glycopeptides. Serious bacterial infections (requiring life-saving aminoglycoside treatment) induce systemic inflammatory responses that also potentiate the degree of ototoxicity and permanent hearing loss. We discuss prospective clinical strategies to protect auditory and vestibular function from aminoglycoside ototoxicity, including reduced cochlear or sensory cell uptake of aminoglycosides, and otoprotection by ameliorating intracellular cytotoxicity.